Exploring Perceptions of Vitamin D Awareness among Clinicians in Local Health Facilities of Pakistan: A Mixed - Method Study - Asma Akhtar; Sobia Nasir; Wali Muhammad; Rabiya Masood; Shireen Mansoor; Saima Masoom Ali (Journal of the Dow University of Health Sciences)
Objective: To assess the knowledge, attitudes, and practices regarding vitamin D among clinicians in local health facilities of Pakistan, and to explore their perceptions through a mixed-method approach. Methods: This mixed-methods study was conducted in local health facilities of Karachi and Multan, from June to September 2024. Clinicians holding MBBS and BDS degrees involved in patient care were included. Quantitative data were collected using the validated Vitamin D Knowledge, Attitude, and Practice questionnaire (D-KAP-38), consisting of 38 items across four domains. Higher mean scores indicated better knowledge, more positive attitudes, and healthier practices related to vitamin D. Qualitative data were gathered through five focus group discussions with 20 clinicians and analyzed using manual thematic analysis. Results: A total of 278 clinicians, the mean age was 30.7 ± 5.1 years. Overall, mean scores of general knowledge 18.39 ±2.91, nutritional knowledge 4.93 ±2.39, attitude 48.61 ±7.49, and practice 30.19 ±4.08, indicating high general knowledge, moderately positive attitudes and practices, but relatively low nutritional knowledge. Female clinicians demonstrated significantly higher nutritional knowledge (p-value =0.016) and healthier practice behaviors (p-value <0.001). MBBS graduates had higher practice scores than BDS (p-value =0.038). Clinicians over 30 years scored higher in nutritional knowledge (p-value =0.010) and attitude (p-value <0.001). Qualitative analysis identified four themes: vitamin D's broader health role, barriers to testing, challenges in prescribing, and recommendations including continuing medical education, public education, and policy support. Conclusion: Clinicians showed good awareness, but gaps in nutrition knowledge and practice highlight the need for targeted education and policy support.